PELATIHAN MEDIA PEMBELAJARAN POWERPOINT BERBASIS ONLINE MENGGUNAKAN CANVA DI SMK SWASTA TRISULA DOLOK SANGGUL - Purba, Arlina Pratiwi; Purba, Angelia Maharani; Sitanggang, Ernie Shinta Yosephine; Simatupang, Eva Malina (ASOSIASI IDEBAHASA KEPRI, 2024)
SMK Swasta Trisula Dolok Sanggul is one of the private schools in Dolok Sanggul. This school has 3 departments, namely (1) Department of Light Vehicle Engineering (Automotive), (2) Audio Video Engineering (Electronics Engineering) and (3) Computer and Network Engineering. The results of learning observations at Trisula Dolok Sanggul Private Vocational School in Humbang Hasundutan Regency show that learning during this pandemic still uses WhatsApp groups to inform students about assignments. This is felt to be less effective for students. Apart from that, teachers at Trisula Dolok Sanggul Private Vocational School are still not optimal in utilizing information technology and the internet as learning media. By conducting more intensive training for teachers and students regarding the use of learning media and the function of media in the learning process, it is hoped that teachers will use digital-based learning media more often, because the use of digital-based learning media will be very beneficial for students in understanding the subject matter even though it has already been implemented. face to face/offline and students are more motivated to take part in these lessons. he conclusions from this activity are:1. Increased use of online-based PowerPoint learning media by teachers to improve student quality 2. Increased student motivation in participating in learning through Powerpoint learning media provided by the teacher 3. Providing 1 unit of ViewSonic SVGA 4000 ANSI LUMENS/HDMI Projector to SMK Swasta Trisula Dolok Sanggul 4. Monitoring is carried out after the implementation of service activities